Callose and reactive oxygen species expressed in sugar cane leaves by mechanical damage of spittlebugs - Pacheco-Coeto, Rosario; Cárdenas-Torres, Luis; Hernández-Rosas, Francisco; Hidalgo-Contreras, Juan Valente; Aquino-Pérez, Gildardo (Revista Mexicana de Ciencias Agrícolas, 2019)
Spittlebugs is considered the main pest insect in sugar cane, this due to mechanical damage caused by the insertion of its stylet in the leaves. This research is focused on the response of the plant to the presence of said hemiptera, which involves the production of callose expressing β-glucans and high presence of reactive oxygen species (ERO) with the reaction of peroxides. These cause cell deaths in the damaged area and limit cell damage. In this document, the presence of callose and ERO is expressed in sugarcane seedlings subjected to spittlebugs infestations. The tissues of the damaged leaves were treated with fluorescent dyes such as aniline blue fluorochrome that adheres to the (1-3) β-glucans of the callose and the CM-H2DCFDA that binds to the intracellular glutathione of ERO by the presence of peroxides. This expression was measured in nanometers based on the intensity of fluorescence expressed by the presence of β-glucans (700 to 7 000 nm) and peroxides expressed between 1 000 to 6 400 nm. These results reveal the real damage caused by the insect’s stylet on the leaf and its effects on the surface and inside the leaf.